Staphylococcus aureus protein A enhances osteoclastogenesis via TNFR1 and EGFR signaling - Mendoza Bertelli, Andrea Cristina (2016)
Staphylococcus aureus is a major causative agent of osteomyelitis in adults and children. The increasing incidence of antimicrobial resistant isolates and the morbidity of this type of infection denote that alternative therapeutic approaches are required. S. aureus protein A interacts with TNFR1 and EGFR expressed at the surface of host cells. Given the importance of TNF-α and EGFR/RANKL crosstalk in enhancing osteoclast differentiation, the aim of this study was to determine the role of protein A in the induction of osteoclastogenesis and bone resorption during staphylococcal osteomyelitis. We determined that protein A plays a critical role in osteoclast differentiation and activation by initiating TNFR1 and EGFR mediated signaling. Moreover, we demonstrated that protein A significantly contributes to increased osteoclast differentiation and activation as well as cortical bone destruction during the course of disease using experimental models of osteomyelitis. Our findings strongly suggest targeting protein A and TNFR1 as an adjunctive strategy to control bone damage during the initial course of S. aureus osteomyelitis.